APPLICATION OF COGNITIVE BEHAVIORAL THERAPY (CBT) THEORY TO IMPROVE SELF-EFFICACY AND MOTIVATION IN MEMORIZING THE QUR'AN - Khomsatur Rohmah; Sukarman Sukarman; Muhammad Khoiruddin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
This research is motivated by the problem of low self-efficacy (self-confidence) in some students who memorize the Qur'an, which has an impact on decreasing motivation and memorization targets. Negative thoughts such as feelings of inadequacy, fear of forgetting, and mental fatigue often hinder the memorization process, as well as cognitive barriers (such as negative thoughts "memorizing is difficult" or laziness) experienced by students in the Qur'an memorization program. The purpose of this study is to explore and analyze the application of Cognitive Behavioral Therapy (CBT) theory as an intervention strategy to increase self-efficacy and motivation in memorizing the Qur'an. The method used is qualitative with a library research approach, which analyzes literature related to CBT, self-efficacy, and motivation to memorize the Qur'an. The results indicate that CBT, which combines cognitive and behavioral principles, is effective in changing dysfunctional thought patterns into more rational ones. The application of CBT techniques such as cognitive restructuring and behavioral techniques (disciplined recitation/repetition) can strengthen students' self-efficacy that they are capable of achieving memorization targets. This study concludes that CBT intervention has the potential to be an appropriate counseling approach in fostering the mentality of tahfidz students to be more disciplined, calm, and motivated.